2003
DOI: 10.1021/jp034723r
|View full text |Cite
|
Sign up to set email alerts
|

Photoblinking of Rhodamine 6G in Poly(vinyl alcohol):  Radical Dark State Formed through the Triplet

Abstract: We investigate the fluorescence intensity of rhodamine 6G in poly(vinyl alcohol) as a function of excitation intensity, illumination time, the presence of oxygen, and temperature. The variations in emissivity (or fluorescence brightness) are attributed to a dark state, which shows populating kinetics resembling those of the triplet state, but a much longer lifetime. We simulate the observed kinetics by a four-level model, in which a long-lived dark state is formed through the triplet as an intermediate state. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
328
3
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(353 citation statements)
references
References 44 publications
20
328
3
2
Order By: Relevance
“…Although we cannot formally rule out the possibility of a long-lived triplet state, our results suggest that the observed dark state is an additional state, subsequent to the triplet intermediate. Potential mechanisms for such a dark state include radical-ion formation and nuclear coordinate movement of the dye [23,24]. Previous studies have reported photoblinking of dye molecules with dark-state lifetimes ranging from milliseconds to tens of seconds [23], but none approaching the length of the Cy5 dark state described here.…”
mentioning
confidence: 60%
“…Although we cannot formally rule out the possibility of a long-lived triplet state, our results suggest that the observed dark state is an additional state, subsequent to the triplet intermediate. Potential mechanisms for such a dark state include radical-ion formation and nuclear coordinate movement of the dye [23,24]. Previous studies have reported photoblinking of dye molecules with dark-state lifetimes ranging from milliseconds to tens of seconds [23], but none approaching the length of the Cy5 dark state described here.…”
mentioning
confidence: 60%
“…It has been noted by Zondervan et al that dark states other than the triplet, like the radical state, can drastically affect photobleaching [16], as now strongly and directly evidenced by the results above. Using single-molecule fluorescence measurements, we cannot distinguish whether electron tunneling takes place from the singlet excited state or from the triplet state [14]. Further experiments, e.g., exploiting the heavy-atom effect to increase population of the triplet state [3], are needed to resolve this issue.…”
Section: Prl 95 097401 (2005) P H Y S I C a L R E V I E W L E T T E mentioning
confidence: 97%
“…Such LD states have been extensively studied on semiconductor nanocrystals [9][10][11][12][13], yet only few studies on other types of single emitters have been reported [4,6,14]. In the case of fluorescent organic molecules, the LD states are discussed in terms of the reversible formation of nonfluorescent photo-oxidation products [7,15], and the formation of radical anions or cations via intersystem crossing [14] or electron tunneling processes [4]. So far, however, data on LD state dynamics in single molecules have been hard to acquire.…”
mentioning
confidence: 99%
“…Curiously, almost every nanoscale fluorescent object is known to exhibit fluorescence blinking. For semiconductor quantum dots and solubilised chromophores, the dominant underlying molecular mechanism was shown to involve ionisation, in the former due to a photoassisted Auger process [27,28] and in the latter, longliving, dark radical states were populated via triplet states [29]. For LHC2, containing 54 chromophores, one might similarly expect radical states to be responsible for fluorescence blinking.…”
Section: Photoactive Control Over the Intrinsic Protein Disordermentioning
confidence: 99%